White light and multicolor emission tuning in Ag nanocluster doped fluorophosphate glasses - Fares, Hssen [UNESP]; Castro, Tarcio [UNESP]; Orives, Juliane Resges [UNESP]; Franco, Douglas Faza [UNESP]; Nalin, Marcelo [UNESP] (Royal Society of Chemistry (RSC), 2017)
The emission properties of Ag nanoclusters (Ag NCs) dispersed in a transparent fluorophosphate glass host have been studied. The as-prepared glass shows that the Ag NCs emit a broad white emission band almost covering the entire visible region. By changing the excitation wavelength it is possible to tune the emission from blue to yellow. The spectral width of the white light is most likely due to the presence of a variety of Ag NCs with different sizes, particularly emitting in the blue, green and red regions. The possible interaction mechanism between the different Ag species was also elucidated. The observed results provide a new platform to acquire a broad band tunable light source.